Josemaría Escrivá de Balaguer, profesor de ética para periodistas: Madrid, 1941 / Josemaría Escrivá de Balaguer, lecturer in Ethics for journalists: Madrid 1941 - Pablo Pérez López (Studia et Documenta)
This is a study of the lectures on Ethics and Professional Morals given by St. Josemaría as part of an official training course for journalists held in Madrid, in 1940-41. It examines the history of the course, his appointment as lecturer, the context in which it took place, the curriculum taught and what is known about his lectures from the outlines he prepared and the testimonies of some of the students. This information is presented in the light of what St. Josemaría thought about the task of professionals working in social communications.